Maximizing Employee Performance through Compensation, Engagement, and Commitment: Memaksimalkan Kinerja Karyawan melalui Kompensasi, Keterlibatan, dan Komitmen - Rachman, Wahyu Fathur; Sumartik, Sumartik (Indonesian Journal of Innovation Studies, 2024)
This quantitative study investigates the combined impact of compensation, employee engagement, and organizational commitment on employee performance at PT. BPR Arta Seruni, Sidoarjo Branch. Utilizing multiple linear regression analysis and a sample of 80 employees, the study reveals that all three factors—compensation, employee engagement, and organizational commitment—positively influence employee performance individually, and collectively have a significant effect. The findings underscore the importance of addressing these factors collectively to enhance employee performance within the banking industry, offering insights for organizational strategies aimed at improving effectiveness and satisfaction among employees, thus contributing to sustainable growth and success. Highlights: 1. Study: Compensation, engagement, commitment impact employee performance in banking.2. Positive effects found individually and collectively.3. Collective focus crucial for employee satisfaction and organizational effectiveness. Keywords: Compensation, Employee Engagement, Organizational Commitment, Employee Performance, Banking Industry